2017
DOI: 10.1038/bdjteam.2017.136
|View full text |Cite
|
Sign up to set email alerts
|

Stress and well-being in dental hygiene and dental therapy students

Abstract: investigate students' motivation to become clinicians and put forward an optimistic view of the role of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
1
7
0
1
Order By: Relevance
“…Student academic characteristics, including higher current academic semester and moving to another city to study were indirectly linked with poor quality of life. Previous research has shown that years of study and distance from hometown were negatively associated with quality of life in medical students through anxiety and lifestyle (Harris et al, 2018 ). The demanding requirements of clinical training and the development of complex communicating skills to deal with patients are important sources of stress among dental students that may explain the decline of student quality of life (Alhajj et al, 2018 ; Elani et al, 2014 ; Gambetta-Tessini, Mariño, Morgan, Evans, & Anderson, 2013 ; Hayes, Hoover, Karunanayake, & Uswak, 2017 ; Naidu et al, 2002 ; Sanders & Lushington, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Student academic characteristics, including higher current academic semester and moving to another city to study were indirectly linked with poor quality of life. Previous research has shown that years of study and distance from hometown were negatively associated with quality of life in medical students through anxiety and lifestyle (Harris et al, 2018 ). The demanding requirements of clinical training and the development of complex communicating skills to deal with patients are important sources of stress among dental students that may explain the decline of student quality of life (Alhajj et al, 2018 ; Elani et al, 2014 ; Gambetta-Tessini, Mariño, Morgan, Evans, & Anderson, 2013 ; Hayes, Hoover, Karunanayake, & Uswak, 2017 ; Naidu et al, 2002 ; Sanders & Lushington, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…University life involves a range of unique opportunities for undergraduate students, including experiencing new physical and social environments as well as developing new social relationships that can potentially influence their well-being and quality of life (Elani et al, 2014 ; Harris, Wilson, Highes, Knevel, & Radford, 2018 ). During this period, students need to adapt to deal with the new challenges and responsibilities, as well as academic demands and pressures encountered in the academic environment (Polychronopoulou & Divaris, 2009 ; Tosevski, Milovancevic, & Gajic, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Elevated stress in particular has been shown to adversely affect dental students’ health and well‐being 11 . On the contrary, dental hygiene students reported high psychological well‐being scores, despite reporting similar levels of stress to that of dental students 12 . The temporary closure of the dental school and postponement of elective dental care per the Governor's executive order, likely represent an additional source of stress to dental/dental hygiene students, especially those in their last year of clinical training yet to complete their graduation requirements.…”
Section: Introductionmentioning
confidence: 99%
“…PSS and DES scales were adopted as they are widely used to estimate the stress levels of dental and dental hygiene students. 1 , 2 , 3 , 4 , 16 , 17 Cronbach's alpha of the Japanese and Chinese version PSS-10 and DES represented good reliability.…”
Section: Discussionmentioning
confidence: 93%